AB1412 Nurses can achieve very good agreement with physicians for joint counts in rheumatoid arthritis – a feasible training method. (23rd January 2014) - Cheung, P.; Dougados, M.; Andre, V.; Balandraud, N.; Chales, G.; Chary-Valckenaere, I.; Chatelus, E.; Dernis, E.; Gill, G.; Gilson, M.; Guis, S.; Mouterde, G.; et al.
Abstract : Background: "Tight control" of rheumatoid arthritis (RA) necessitates regular disease activity assessment using clinical joint counts. However, joint counts take time, and are not always performed in busy clinics [1]. Nurses are now increasingly involved in joint count assessment but training for joint counts is not standardised. Objectives: Evaluate an effective method of teaching nurses to perform 28-joint counts (tender and swollen). Methods: This was the first phase of a national study (COMEDRA).Twenty nurses from university rheumatology centers without any joint count experience were allocated to a rheumatologist from their center (trainer). Training program consisted of 2 phases: Phase 1 was a centralized 4 hour training session, with (a) a one-hour lecture and demonstration, and (b) practical sessions on patients with the trainers. Phase 2 involved further practice on 20 patients in their own hospitals; with 10 nurses randomized to (i) one additional comparative assessment with the trainer for patient 10, and 10 nurses to (ii) no further training (but a separate assessment by the trainer at patient 10). Strength of agreement was measured between each nurse and his/her trainer, through prevalence adjusted biased adjusted kappa (PABAK); poor agreement <0.20, Fair agreement 0.20-0.40, Moderate Agreement 0.40-0.60, Good agreement 0.60-0.80, Very good agreement 0.80-1.00. Results: Mean pooled PABAK for swollen joint agreement at baseline was 0.67 (95%CI 0.57, 0.77). By the end of the training program, this increased to 0.82 (95%CI 0.80, 0.93). There were successive improvements in swollen joint PABAK at each assessment point and by the end of training; everyone had achieved a swollen joint PABAK >0.60 with their trainer except 2 nurses. Most of the improvement was seen during Phase 2. In Phase 2, swollen joint agreement improved for those who had the additional training; from PABAK 0.71 (95%CI 0.57, 0.84) to 0.83 (95%CI 0.70, 0.96), but not for those who had no further training; PABAK 0.79 (95%CI 0.53, 1.0) to 0.80 (95%CI 0.62, 0.99). The agreement for tender joints remained very good throughout Phase 1 and 2 with PABAK >0.80 at each assessment point. Conclusions: Nurses can effectively learn how to perform swollen and tender joint counts with this teaching method. Swollen joint agreement improved significantly. This method can be practically applied in the clinical setting. References: Pincus T, Segurado OG. Ann Rheum Dis 2006; 65: 820-2. Disclosure of Interest: None Declared